PyRosetta Jupyter Notebooks Teach Biomolecular Structure Prediction and Design - Le, Kathy H.; Adolf-Bryfogle, Jared; Klima, Jason C.; Lyskov, Sergey; Labonte, Jason W.; Bertolani, Steven; Burman, Shourya S. Roy; Leaver-Fay, Andrew; Weitzner, Brian D.; Maguire, Jack; Rangan, Ramya; Adrianowycz, Matt A.; et al. (Biophysicist (Rockville, Md.), 2021)
Biomolecular structure drives function, and computational capabilities have progressed such that the prediction and computational design of biomolecular structures is increasingly feasible. Because computational biophysics attracts students from many different backgrounds and with different levels of resources, teaching the subject can be challenging. One strategy to teach diverse learners is with interactive multimedia material that promotes self-paced, active learning. We have created a hands-on education strategy with a set of 16 modules that teach topics in biomolecular structure and design, from fundamentals of conformational sampling and energy evaluation to applications, such as protein docking, antibody design, and RNA structure prediction. Our modules are based on PyRosetta, a Python library that encapsulates all computational modules and methods in the Rosetta software package. The workshop-style modules are implemented as Jupyter Notebooks that can be executed in the Google Colaboratory, allowing learners access with just a Web browser. The digital format of Jupyter Notebooks allows us to embed images, molecular visualization movies, and interactive coding exercises. This multimodal approach may better reach students from different disciplines and experience levels, as well as attract more researchers from smaller labs and cognate backgrounds to leverage PyRosetta in science and engineering research. All materials are freely available at https://github.com/RosettaCommons/PyRosetta.notebooks .